Global studies directory : people, organizations, publications - Chumakov, Alexander Nikolaevich.; Ilyin, Ilya Vyacheslavovich.; Mazour, Ivan Ivanovich. (Value Inquiry Book Series, 2017)
Publication of the Global Studies Directory represents an unprecedented project in world practice. Based on the professional assessment by a large international team of experts, the Directory offers information on the most well-known scholars, political and public figures who have made outstanding contributions to the establishment and development of global studies or made a fundamental impact on the formation of global world. The Directory also contains comprehensive information about organizations, periodicals and special literature of direct relevance to the theory and practice of globalization and fully demonstrates the state of affairs in the field of study on a global level. This project is a continuation of many years of research which first resulted in the publication of the Global Studies Encyclopedic Dictionary , the companion publication to the Directory.